Analysis of shale pore structure characteristics based on nitrogen adsorption experiment and fractal FHH model: a case study of 7th member of Triassic Yanchang Formation in Huachi area, Ordos Basin - Cheng AN; Guangdi LIU; Mingliang SUN; Fuliang YOU; Zixin WANG; Yushun CAO (Shiyou shiyan dizhi, 2023)
Pore structure, as the focus of shale reservoir research, has important influence on the occurrence of shale oil. In this paper, 10 shale core samples from the 7th member of Triassic Yanchang Formation (Chang 7 member) in Huachi area, Ordos Basin were selected to carry out scanning electron microscope (SEM) observation and low-temperature nitrogen adsorption experiment, and the fractal dimension was calculated to quantitatively characterize the pore structure of shale in the research area combined with fractal FHH model. On this basis, the relationship between fractal dimension and pore structure parameters and oil-bearing parameters was discussed, and the main influencing factors of pore development of shale in the Chang 7 member were determined. The results show that the shale of the Chang 7 member in Huachi area has high organic matter abundance, which are good-to-excellent source rocks mainly composed of quartz and clay minerals, with good oil-bearing property (up to the middle oil-bearing level) and mobility. The reservoir space is dominated by intergranular pores, intragranular pores and a small amount of organic pores. There are two types of pore morphology, namely, parallel plate-shaped slit+unilateral slit and ink bottle-shaped + parallel plate-shaped slit. The pores are mainly micropores and mesopores, with macropores less developed. Most samples have fractal characteristics. The fractal dimension D1 of small pores is between 2.264 7 and 2.714 9, and the fractal dimension D2 of large pores is between 2.373 3 and 2.77 7. Among them, D2 has a good correlation with surface area, pore volume, average pore diameter and S1, which can characterize the development characteristics of pore structure and oil-bearing property of shale, while D1 can only characterize the mobility of shale oil. The pore development of shale is mainly controlled by TOC and quartz content, and has a certain relationship with feldspar content, while clay mineral content is not the main influencing factor.